Rational Use of Antibiotics and Requisition of Pharmacist - Said, Muhammad Soaib; Saleem, Iqra; Hashmi, Asif Mehmood; Izharullah; Khan, Amer Hayat; Khan, Amjad; Iftikhar, Muhammad Hassnain; Latif, Mohsin (International Journal of Natural Medicine and Health Sciences, 2022)
ABSTRACT Background: Direct consequence of microbes developing resistance against antibiotics is prolonged hospitalization, increased treatment cost and duration. Increased duration of hospitalization causes prolonged use antibiotics which results towards side effects. Primary Study Objective: The purpose of antibiotics use is either to kill the microbes (bactericidal) or slows down their growth (bacteriostatic). Irrational use of antibiotics makes them do their exact opposite. Instead of killing microbes or slowing down their growth, it allows microbes to develop resistance against antibiotics. Methods/Design: An observational concurrent study was performed in which data was collected. Individuals were interviewed using structured questionnaire. Percentage of rationality and irrationality of antibiotics use was observed. Additionally percentage of prescribed class of antibiotics was also observed in patients. Setting: Health care system includes: Quaid e Azam International Hospital Islamabad, Benazir Hospital Rawalpindi, CMH Rawalakot AJK, Amna Hospital Rawalakot AJK, DHQ Kotli AJK Pakistan. Participants: This study was conducted on 100 patients of different health care systems, to whom antibiotics were prescribed. Most patients interviewed were female with UTI aged above 30 and adults male with RTI or chest infection. Intervention: Different patients were interviewed in different hospital settings to evaluate the rational use of antibiotics Primary Outcome Measures: Rational use of antibiotics is using antibiotics according to the guidelines provided by WHO. Major guidelines include: patient receives medication according to their clinical needs, dosage appropriate to the individual requirements and for specific duration of time with low cost. Results: 47 percent of these patients were using antibiotics rationally and 53 percent were taking antibiotics medication irrationally. The most prevalent form of irrational use was patients without counseling about the antibiotics use. Patients with poor knowledge about the use of antibiotics were 84 among the 100. Irrational use of antibiotics in the form of pre-mature discontinuation was reported 56 patients among the 100. Patient who irrationally use antibiotics as OTC or Self medications were 38 among the 100. Conclusion: Major form of irrationality found in the study was no proper counseling provided to the patients by specialist physician or Pharmacists. The reason we critically observed for this is the burden of patients on physicians due to which they are not able to properly guide patients. The community on which this study was conducted has a major absence of pharmacist. Dispensers and pharmacy technicians are performing pharmacist’s tasks. Absence of pharmacist leads to dosage dispensing errors, lack of professional medical counseling, and no drug utilization review